2012
DOI: 10.1177/0093650212441794
|View full text |Cite
|
Sign up to set email alerts
|

Partisan Evaluation of Partisan Information

Abstract: One recent and conspicuous change in the U.S. media landscape has been the shift toward more markedly partisan news content. At the same time, data suggest that the media audience has become more polarized across a wide array of controversial and politicized issues. Recruiting from a group of highly polarized opponents of childhood vaccinations, this study employed a 3 (content bias) × 2 (partisan vs. neutral participants) × 2 (information source) experimental design to examine audience perceptions of informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 26 publications
2
32
0
1
Order By: Relevance
“…This finding suggests respondents brought to mind other concerns about vaccines to defend their anti-vaccine attitudes, a response that is broadly consistent with the literature on motivated reasoning about politics and vaccines. [25][26][27][28] In addition, our data provide little evidence that messages emphasizing the risks of vaccine-preventable diseases were effective in promoting vaccination intent. This finding is consistent with previous studies finding mixed effects of lossframed messages and fear appeals on vaccination and other preventive health behaviors.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding suggests respondents brought to mind other concerns about vaccines to defend their anti-vaccine attitudes, a response that is broadly consistent with the literature on motivated reasoning about politics and vaccines. [25][26][27][28] In addition, our data provide little evidence that messages emphasizing the risks of vaccine-preventable diseases were effective in promoting vaccination intent. This finding is consistent with previous studies finding mixed effects of lossframed messages and fear appeals on vaccination and other preventive health behaviors.…”
Section: Discussionmentioning
confidence: 66%
“…[22][23][24] The problem is that people often interpret evidence in a biased fashion. [25][26][27][28] As a result, corrective information about controversial issues may fail to change factual beliefs or opinions among respondents who are most likely to be misinformed. 22,29 In some cases, corrections can even make misperceptions worse.…”
Section: Resultsmentioning
confidence: 99%
“…Two-sided messages may be more difficult to process because readers have to deal with conflicting arguments (Hale, Mongeau, & Thomas, 1991). Also, readers' evaluation of the presented headlines may not always be objective: Research on the hostile media effect (Vallone, Ross, & Lepper, 1985) showed that partisans perceive balanced articles as biased against their point of view (e.g., Gunther, Edgerly, Akin, & Broesch, 2012), which would decrease the likelihood of selection. In fact, in a study in which participants were able to choose between articles with conservative, liberal, or neutral headlines (Jang, 2014), neutral articles were selected less frequently than articles that were in line with readers' political views.…”
Section: Message Cues: Selection Of Consistent Inconsistent and Balmentioning
confidence: 99%
“…Findings point toward a "relative hostile media effect": Perceptions of bias in opinionated news are strongest among those with incongruent political preferences, whereas those who hold views in line with the source, perceive less bias in such opinionated news or fail to see a bias at all (Arceneaux et al, 2012;Coe et al, 2008;Feldman, 2011b;Gunther, Edgerly, Akin, & Broesch, 2012). Hence, we expect the following: H 2a : Opinionated news evokes stronger bias perceptions than objective news, especially among people with incongruent political preferences.…”
Section: Opinionated News and The Consequences Of The Hostile Media Pmentioning
confidence: 92%